PENGARUH KOMUNIKASI DAN KOMITMEN ORGANISASI TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR CAMAT LAMBU KABUPATEN BIMA - Ayunda Rusdyanti; Firmansyah Kusumayadi (Sharing: Journal of Islamic Economics Management and Business, 2023)
This study aims to find out and analyze the effect of communication and organizational commitment on employee morale at the Lambu sub-district office, Bima district. Types of associative research . research instrument using a Likert scale questionnaire. The population used in this study were all employees at the Lambu sub-district office as many as 60 respondents. The sample in this study were all employees at the Lambu sub-district office as many as 60 respondents. The sampling technique uses saturated sampling technique, saturated sampling technique is a sampling technique that uses all members of the population to be sampled. Data collection techniques in this study were observation, interviews, questionnaires and literature study. Data analysis techniques using validity test, reliability test, classical assumption test, multiple regression, multiple correlation coefficient, t test and f test. The results showed that communication and organizational commitment had a positive and significant simultaneous effect on morale at the Lambu sub-district office, Bima district, financial performance.